La comunicación digital para la productora de radio “HDF” de la ciudad de Loja - Guarnizo Toledo, Israel Geovanny (2016)
The thesis called DIGITAL COMMUNICATION FOR THE PRODUCTION OF RADIO "HDF" of the city of Loja. It has been structured and developed according to the regulations of academic regime of the National University of Loja. The problem arose on the basis of providing a response to the question How to implement digital communications radio producer "HDF" so that the information generated immediately reach his listeners? The main objective was to find alternatives to facilitate immediate access to sports information, by implementing a digital medium that can generate news radio producer "HDF". The methods used were scientific, inductive-deductive, descriptive and analytic-synthetic method and materials used are cell phone, camera, laptop and data logging. Meanwhile the techniques used and the survey interview. The findings show that the producer "HDF" is an important host of listeners, the vast majority have internet access, meaning that the computer mechanism through social networks like facebook and twitter has become a source of immediate information . The main results after the research process is: 83% of respondents felt it was important to implement a web page, and considering that 79% of respondents listen to sports information generated by the producer "HDF" and having Internet access to 73%; and knowing that 71% of respondents use Facebook as the primary tool of digital communication, 13% and 10% twitter WhatsApp, you should implement a sports website.